Pengaruh Likuiditas, Profitabilitas, Struktur Modal, Kepemilikan Institusional, dan Ukuran Perusahaan Terhadap Financial Distress: Studi pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Berlyana Eka Azzahra; Muhamad Syaichu (Diponegoro Journal of Management, 2026)
This study aims to analyze the effect of liquidity (Quick Ratio), profitability (Net Profit Margin), capital structure (Debt to Equity Ratio), institutional ownership, and firm size (Ln Total Assets) on the probability of financial distress in property and real estate sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Financial distress is proxied using the Interest Coverage Ratio (ICR) in the form of a dummy variable, where companies are categorized as experiencing financial distress if ICR < 1. The research sample consists of 23 companies with a total of 115 observations selected through purposive sampling technique. The analytical method used is binary logistic regression with EViews 12 software. The results show that partially, profitability (Net Profit Margin) and firm size (Ln Total Assets) have a negative and significant effect on the probability of financial distress, indicating that the higher the profitability and the larger the firm size, the lower the probability of financial difficulties. Meanwhile, liquidity (Quick Ratio), capital structure (Debt to Equity Ratio), and institutional ownership have no significant effect. Simultaneously, all five independent variables have a significant effect on financial distress with a Prob (LR Statistic) value of 0.0000. The logistic regression model has a prediction accuracy of 81.74% and a McFadden R-squared value of 33.57%, indicating that the model is good in explaining the variation in financial distress. These findings imply that companies with low profitability and small business scale have a higher risk of financial distress, thus requiring serious attention from management, investors, creditors, and regulators in formulating preventive strategies, investment decisions, and supervisory policies for the property and real estate sector.